Prenatal Diagnosis Of Congenital Heart - Huertas-Tacchino, Erasmo (2019)
Presenting the case of a primigravida patient with no risk factors to which it is detected congenital heart disease muscular type VSD is performed which is confirmed by neonatal echocardiography at birth.